MOTIVASI ORANG TUA PETANI SAYUR DALAM MENINGKATKAN KEGIATAN BELAJAR ANAKNYA DI SD NEGERI 098 KELURAHAN KULIM KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Flora, Dwi Elsi; Jas, Jasfar; Maemunaty, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine Motivation Parents Vegetable Farmers in Developing Learning Activities son Elementary School In 098 In Village Kulim District of Tenayan Raya Pekanbaru. This research is descriptive with quantitative approach.This is a descriptive study with a quantitative approach that aims to describe the results of research by the numbers. Mechanical sampling using simple random sampling (simple random sampling).Data collection techniques in this research is by using a questionnaire, which amounted to 41 items a statement. Data obtained from respondents who were 30 to 83 samples for testing and research samples. After the questionnaire in the trial, there are three items that are not valid, and researchers discard all statements that are not, so that the whole instrument otherwise reliable with a Cronbachs alpha = 0.95.The findings of the two indicators can be concluded that both indicators can be said to be relatively high. ntrinsic motivation is high because parents vegetable growers discount high intrinsic motivation to improve their learning activities. Whereas extrinsic motivation factor is high because parents vegetable growers memlki high extrinsic motivation in improving their learning activities. So the most dominant indicator between intrinsic motivation and extrinsic motivation is intrinsic motivation.Key words: Motivation Parents Vegetable Farmers in Developing Learning Activities son